Cilampuc Celvarukku Ṭākṭar paṭṭam - Meykaṇṭār, Ti. Va. (Tillaiviṭaṅkaṉ Varatarāja), 1938- (Pūṅkoṭi Patippakam, 1980)
Souvenir, published on the occasion of the conferring of the degree of D. Litt. on M.P. Sivagnanam, b. 1906, Tamil scholar and sociopolitical activist; includes excerpts from speeches delivered by renowned Tamil litterateurs and educationalists on the occasion.